The importance of palliative care in geriatric medicine - Soares, Isabela De Carvalho; Karaja, Leila Ismail Hamed; Morais, Maria Clara Meira; Pereira, Maria Clara Cardoso; Costa, Raphaela Serafin Rulli (Seven Editora, 2023)
Introduction: The world is going through a phase of demographic transition, with an inversion of the age pyramid, and increasing population aging. Thus, palliative care becomes increasingly necessary, and it is important to deepen this area of knowledge, identifying the role of each professional within the multidisciplinary team and the bioethical principles of this specialty. It is also central to identifying the main difficulties for its implementation so that these obstacles can be tackled. In convergence with the theme addressed, in the book "Knocking on Heaven’s Door" the discussion about the limit between the use of medical technology and the humanized form of treatment is noticeable. Objective: This article aims to explain the importance of geriatric palliative care due to population aging, as well as the role of the physician in this area of activity and its professional characteristics that should be prevalent. Finally, it seeks to identify the main challenges for the implementation of this specialty, addressing the importance of family involvement and ethics throughout the process. Methodology: Cross-sectional studies, articles, and statistical data published between 2013 and 2021 were used. The ponies used were Scientific Electronic Library Online (SciELO), Medical Literature Analysis and Retrieval System Online (MEDLINE/Pubmed), Google Scholar, and data obtained through official websites of the Brazilian Government, using the descriptors "palliative cares", "geriatrics", "slow medicine" and "bioethics". Conclusion: It is concluded that the demographic increase in the elderly population culminated in an increase in the need for palliative care. Because of this, bioethics and its relationship with curative tracts are discussed in an attempt to prolong life to the detriment of a comfortable life. DOI: https://doi.org/10.56238/colleinternhealthscienv1-082